Design, Analysis and Fabrication of a Novel Transverse Flux Permanent Magnet Machine with Disk Rotor - Azarinfar, Hosein; Aghaebrahimi, Mohammad (Applied sciences, 2017)
The purpose of this paper is to propose a novel design for the transverse flux permanent magnet (TFPM) disk-rotor generator with E and I-shaped cores (TFPMDEIG). Disk-shape structure increases the machine’s power factor, allows for high rotational speeds, decreases centrifugal force over permanent magnets, and is employed in wind turbines, due to its compact structures. As for other advantages for this structure, one can point to the fact that there are as many windings as machine’s pole pairs; these windings become parallel by observing the polarity. In other words, the total power of this machine is distributed between pole pairs, increasing the overall reliability of the machine. In this paper, first, the initial design algorithm and the basic formulas governing the behavior of the proposed structure using the equivalent magnetic circuit for each pole are provided, and the three-dimensional finite element method (3D-FEM) is used for verification of the algorithm. To validate the simulation results (3D-FEM), then, a prototype has been fabricated and experienced. The experimental results are in good agreement with simulation results.